The Impact of Welfare Reform on Leaver Characteristics, Employment and Recidivism - William J. Carrington; Peter R. Mueser; Kenneth R. Troske (Institute for the Study of Labor (IZA), 2002)
Welfare reform has transformed the U.S. cash assistance program for single parents and their children. Although there remains substantial uncertainty about the importance of reform in producing the subsequent decline in the welfare caseload, even less is known about its impact on the experiences and well being of former welfare recipients. The analysis here focuses on the characteristics and employment of welfare recipients in the state of Missouri over the period 1990-1999. We find that there has been little change in the observable characteristics of those entering, on, or leaving welfare, but there has been a dramatic growth in the importance of employment for all these groups. We also examine the dynamics of employment and welfare recidivism comparing cohorts of leavers prior to and after welfare reform. We find that after welfare reform leavers are much more likely to be working, have higher total earnings, work for employers with similar characteristics, and are less likely to return to welfare. These results suggest that welfare reform has not materially harmed welfare recipients.
Keywords: I3; J0; 330; welfare reform; employment dynamics; Sozialhilfe; Reform; Wirtschaftspolitische Wirkungsanalyse; Sozialhilfeempfänger; Arbeitsangebot; Beschäftigungseffekt; Schätzung; Missouri <Staat>